The Importance of Teaching Vocabulary (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
The article focuses on the importance and benefits of teaching vocabulary to acquire a new language. The goal of this article is to motivate language learners to learn vocabulary as a part of full learning process although it is often taught as a separate skill from other skills.